2020
DOI: 10.1177/2192568220978225
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Management and Outcome of Delayed Deep Surgical Site Infection Following Spinal Deformity Surgery: 20-Year Experience at a Single Institution

Abstract: Study Design: A retrospective study. Objectives: To investigate the incidence, management and outcome of delayed deep surgical site infection (SSI) after the spinal deformity surgery. Methods: This study reviewed 5044 consecutive patients who underwent spinal deformity corrective surgery and had been followed over 2 years. Delayed deep SSI were defined as infection involving fascia and muscle and occurring >3 months after the initial procedure. An attempt to retain the implant were initially made for all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 29 publications
2
17
1
1
Order By: Relevance
“…Although IR was curative in our cohort at the latest follow-up, IE offered better maintenance of correction and improved sagittal profile with equivalent reinfection risk and potentially improved overall health-related quality-of-life outcomes. Our study suggests, as have others, that removal involves a risk of deformity progression for which patients may require revision 4,8–11 …”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Although IR was curative in our cohort at the latest follow-up, IE offered better maintenance of correction and improved sagittal profile with equivalent reinfection risk and potentially improved overall health-related quality-of-life outcomes. Our study suggests, as have others, that removal involves a risk of deformity progression for which patients may require revision 4,8–11 …”
Section: Discussionsupporting
confidence: 78%
“…Although several authors have studied infection after spinal arthrodesis, 6,8–14 evidence is limited regarding the superiority of results obtained with spinal implant removal (IR) vs. implant exchange (IE). Several studies suggest that, although IR and short-term antibiotic therapy are curative, patients may experience deformity progression 1,5,8–10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Частота развития ИОХВ в вертебрологии колеблется от 2,1 до 16,3%, при этом в общей структуре ИОХВ развитие глубокой периимплантной инфекции как самостоятельной нозологической формы инфекционного осложнения регистрируется с частотой до 20% [8,25]. Согласно временной периодизации V. Prinz и P. Vajkoczy, принято выделять раннюю (ограничена 6 нед.…”
Section: Discussionunclassified
“…Infections involving spinal instrumentation are associated with greater rates of disability [2][3][4][5]. Recent publications describe the results of implant removal with an increased risk of collapse of the disk space, loss of lordosis, and pseudarthrosis [6,7]. Previous studies have reported that complications following treatment are a burden not only to patients and healthcare professionals but also to the healthcare system [8].…”
Section: Introductionmentioning
confidence: 99%